Genetic diversity and maternal origin of Northeast African and South American donkey populations. (10th March 2019) - Xia, X.; Yu, J.; Zhao, X.; Yao, Y.; Zeng, L.; Ahmed, Z.; Shen, S.; Dang, R.; Lei, C.
Summary: To investigate the mtDNA variation and origin of maternal lineages in South American donkeys and to reassess the domestication of donkeys in northeast Africa, we analyzed sequences (489 bp of the D‐loop) from 323 domestic donkeys sampled from Peru, Brazil, Ethiopia and Egypt. Altogether, the 323 sequences displayed 53 different haplotypes (45 in Ethiopia, 14 in Egypt, eight in Peru and six in Brazil). Among the four populations, Egyptian donkeys possessed the highest haplotype diversity (0.910 ± 0.032), followed by Brazilian donkeys (0.879 ± 0.060). The Clade I haplotypes dominated in Peruvian donkeys (65%), whereas Clade II haplotypes dominated in Brazilian donkeys (67%). Estimates of F ST values showed a high genetic differentiation between Peruvian and Brazilian donkey populations ( F ST = 0.4066), which could be explained by the complex introduction history of South American donkeys. Phylogeographic analysis indicates that northeast Africa could be the most probable domestication center for Clade I donkeys. Analysis of molecular variance confirmed a weak genetic structure in domestic donkey populations among four continents (Europe, Asia, Africa and South America).